Anticoagulation Prescription and Outcomes in Relation to Renal Function in Patients with Atrial Fibrillation: Results from GLORIA-AF - van der Wall, Sake J.; Teutsch, Christine; Dubner, Sergio J.; Diener, Hans-Christoph; Halperin, Jonathan L.; Ma, Chang Sheng; Rothman, Kenneth J.; Paquette, Miney; Zint, Kristina; França, Lionel Riou; Lu, Shihai; Lip, Gregory Y. H.; Huisman, Menno V.; on behalf of the GLORIA-AF Investigators; Abban, Dzifa; Abdul, Nasser; Abelson, Mark; Ackermann, Alan; Adams, Fran; Adams, Luthando; Adragão, Pedro; Ageno, Walter; Aggarwal, Rajesh; Agosti, Sergio; Aguila Marin, Javier; Aguilar, Francisco; Aguilar Linares, Julio Alberto; Aguinaga, Luis; Ahmad, Zia; Ainsworth, Paul; Al Ghalayini, Kamal; Al Ismail, Saad; Alasfar, Abdelfatah; Alawwa, Abdul; Al-Dallow, Raed; Alderson, Lisa; Alexopoulos, Dimitrios; Ali, Abdullah; Ali, Malik; Aliyar, Pareed; Al-Joundi, Tammam; Al Mahameed, Soufian; Almassi, Hossein; Almuti, Khalid; Al-Obaidi, Mohamed; Alshehri, Mohamed; Altmann, Ute; Alves, Alvaro Rabelo, Jr; Al-Zoebi, Ayham; Amara, Walid; Amelot, Mathieu; Amjadi, Nima; Ammirati, Fabrizio; Andrawis, Nabil; Angoulvant, Denis; Annoni, Giorgio; Ansalone, Gerardo; Antonescu, Sorin Alexandru; Ariani, Mehrdad; Arias, Juan Carlos; Armero, Sébastien; Arora, Rohit; Arora, Chander; Ashcraft, William; Aslam, M. Shakil; Astesiano, Alfredo; Audouin, Philippe; Augenbraun, Charles; Aydin, S.; Azar, Rabih; Azim, Abul; Aziz, Shahid; Backes, Luciano Marcelo; Baig, Mirza; Bains, Suchdeep; Bakbak, Asaad; Baker, Seth; Bakhtiar, Karim; Bala, Richard; Banayan, Jonathan; Bandh, Stellan; Bando, Shigenobu; Banerjee, Subhash; Bank, Alan; Barbarash, Olga; Barón, Gonzalo; Barr, Craig; Barrera, Carlos; Barton, John; Basic Kes, Vanja; Baula, Giovanni; Bayeh, Hamid; Bazargani, Nooshin; Behrens, Steffen; Bell, Alan; Benezet-Mazuecos, Juan; Benhalima, Bouziane; Berdagué, Philippe; Berg van den, B. J.; Bergen van, P. F.M.M.; Berngard, Edvard; Bernstein, Richard; Berrospi, Percy; Berti, Sergio; Bertomeu, Vicente; Berz, Andrea; Bettencourt, Paulo; Betzu, Robert; Beyer-Westendorf, Jan; Bhagwat, Ravi; Black, Toby; Blanco Ibaceta, Jorge Hugo; Bloom, Stephen; Blumberg, Edwin; Bo, Mario; Bockisch, Valerie; Bøhmer, Ellen; Bongiorni, Maria Grazia; Boriani, Giuseppe; Bosch, Ralph; Boswijk, D. J.; Bott, Jochen; Bottacchi, Edo; Bracic Kalan, Marica; Brandes, Axel; Bratland, Bjørn; Brautigam, Donald; Breton, Nicolas; Brouwers, P. J.A.M.; Browne, Kevin; Bruguera, Jordi; Brunehaut, Myriam; Brunschwig, Claude; Buathier, Hervé; Buhl, Aurélie; Bullinga, John; Butcher, Kenneth; Cabrera Honorio, Jose Walter; Caccavo, Alberto; Cadinot, Didier; Cai, Shanglang; Calvi, Valeria; Camm, John; Candeias, Rui; Capo, James, Jr.; Capucci, Alessandro; Cardoso, Juliano Novaes; Carlos Duarte Vera, Yan; Carlson, Brian; Carvalho, Paula; Cary, Susanna; Casanova, Rene; Casu, Gavino; Cattan, Simon; Cavallini, Claudio; Cayla, Guillaume; Cha, Tae Joon; Cha, Kwang Soo; Chaaban, Said; Chae, Jei Keon; Challappa, Krishnan; Chand, Sunil; Chandrashekar, Harinath; Chang, Mark; Charbel, Paul; Chartier, Ludovic; Chatterjee, Kausik; Cheema, Aamir; Chen, Shih-Ann; Chevallereau, Pierre; Chiang, Fu-Tien; Chiarella, Francesco; Chih-Chan, Lin; Cho, Yong Keun; Choi, Dong Ju; Chouinard, Guy; Hoi Fan Chow, Danny; Chrysos, Dimitrios; Chumakova, Galina; Chuquiure Valenzuela, Eduardo Julián José Roberto; Cieza-Lara, Tomas; Cindea Nica, Violeta; Ciobotaru, Vlad; Cislowski, David; Citerne, Olivier; Claus, Matthias; Clay, Anthony; Clifford, Piers; Cohen, Serge; Cohen, Andrew; Colivicchi, Furio; Collins, Rónán; Compton, Steve; Connors, Sean; Conti, Alberto; Contreras Buenostro, Gabriel; Coodley, Gregg; Cooper, Martin; Corbett, Lynn; Corey, Oran; Coronel, Julián; Corrigan, John; Cotrina Pereyra, Rosa Ysabel; Cottin, Yves; Coutu, Benoit; Cracan, Aurel; Crean, Peter; Crenshaw, James; Crijns, H. J.G.M.; Crump, Charles; Cucher, Fred; Cudmore, David; Cui, Lianqun; Culp, John; Darius, Harald; Dary, Patrick; Dascotte, Olivier; Dauber, Ira; Davee, Thomas; Davies, Ruth; Davis, Gershan; Davy, Jean-Marc; Dayer, Mark; De La Briolle, Axel; de Mora, Manuel; De Teresa, Eduardo; De Wolf, Luc; Decoulx, Eric; Deepak, Sasalu; Defaye, Pascal; Del-Carpio Munoz, Freddy; Delic Brkljacic, Diana; Deluche, Laurent; Destrac, Sylvain; Deumite, N. Joseph; Di Legge, Silvia; Dibon, Olivier; Diemberger, Igor; Dillinger, Jean; Dionísio, Pedro; Naydenov, Stefan; Dotani, Imran; Dotcheva, Elena; D'Souza, Anthony; Dubrey, Simon; Ducrocq, Xavier; Dupljakov, Dmitry; DuThinh, Vuong; Dutra, Oscar Pereira; Dutta, Dipankar; Duvilla, Nathalie; Dy, Johnny; Dziewas, Rainer; Eaton, Charles; Eaves, William; Ebinger, Matthew; Eck van, J. W.M.; Edwards, Tim; Egocheaga, Isabel; Ehrlich, Clifford; Eisenberg, Steven; El Hallak, Abdel; El Jabali, Adnan; El Mahmoud, Rami; El Shahawy, Mahfouz; Eldadah, Zayd; Elghelbazouri, Fouad; Elhag, Omar; El-Hamdani, Mehiar; Elias, Darlene; Ellery, Adam; El-Sayed, Hassan; Elvan, A.; Erickson, Bernard; Espaliat, Eric; Essandoh, Louis; Everington, Tamara; Evonich, Rudolph, III; Ezhov, Andrey; Fácila, Lorenzo; Farsad, Ramin; Fayard, Maxime; Fedele, Francesco; Ferreira, Luis Gustavo Gomes; Ferreira, Daniel; Ferreira Santos, José; Ferrier, Anna; Finsen, Alexandra; First, Brian; Fisher, Raymond; Floyd, John; Folk, Thomas; Fonseca, Catarina; Fonseca, Luisa; Forman, Steven; Forsgren, Magnus; Foster, Malcolm; Foster, Nathan; Frais, Michael; Frandsen, Brad; Frappé, Thierry; Freixa, Ramon; French, William; Freydlin, Marina; Frickel, Siegfried; Fruntelata, Ana Gabriela; Fujii, Shigeru; Fujino, Yusuke; Fukunaga, Hiroshi; Furukawa, Yutaka; Gabelmann, Matthias; Gabris, Michael; Gadsbøll, Niels; Galin, Pavel; Galinier, Michel; Ganim, Ricky; Garcia, Ronnie; Garcia Quintana, Antonio; Gartenlaub, Olivier; Genz, Conrad; Georger, Frédéric; Georges, Jean-Louis; Georgeson, Steven; Ghanbasha, Ali; Giedrimas, Evaldas; Gierba, Mariusz; Gillespie, Eve; Giniger, Alberto; Gkotsis, Alexandros; Gmehling, Joachim; Gniot, Jacek; Goethals, Peter; Goldberg, Ronald; Goldmann, Britta; Goldscher, David; Golitsyn, Sergey; Gomez Lopez, Efrain Alonso; Gomez Mesa, Juan Esteban; Gonzalez, Efrain; Gonzalez Cocina, Emilio; Gonzalez Juanatey, Carlos; Gorbunov, Vladimir; Gordon, Brian; Gorka, Hervé; Gornick, Charles; Gorog, Diana; Goss, Franz; Götte, Andreas; Goube, Pascal; Goudevenos, Ioannis; Goulden, Dudley; Graham, Brett; Grande, Angel; Greco, Cesare; Green, Martin; Greer, Gerald; Gremmler, Uwe; Grena, Paul; Grinshstein, Yuriy; Grond, Martin; Gronda, Edoardo; Grondin, Francois; Grönefeld, Gerian; Groot de, J. R.; Guardigli, Gabriele; Guarnieri, Thomas; Guevara Caiedo, Carolina; Guignier, Alexandre; Gulizia, Michele; Gumbley, Michael; Gupta, Dhiraj; Hack, Terrence; Haerer, Winfried; Hakas, Joseph; Hall, Christian; Hampsey, James; Hananis, Georgios; Hanbali, Basel; Handel, Franklin; Hargrove, Joe; Hargroves, David; Harris, Kenneth; Hartley, David; Haruna, Tetsuya; Hata, Yoshiki; Hayek, Emil; Healey, Jeff; Hearne, Steven; Heggelund, Geir; Hemels, M. E.W.; Hemery, Yann; Henein, Sam; Henz, Benhur; Her, Sung-Ho; Hermany, Paul; Hernandes, Mauro Esteves; Higashino, Yorihiko; Hill, Michael; Hisadome, Tetsuo; Hishida, Eiji; Hitchcock, James; Hoffer, Etienne; Hoghton, Matthew; Holmes, Clare; Hong, Suk Keun; Houppe Nousse, Marie-Paule; Howard, Victor; Hsu, Li Fern; Huang, Chi-Hung; Huckins, David; Huehnergarth, Kier; Huizenga, A.; Huntley, Richard; Hussein, Gamal; Hwang, Gyo-Seung; Igbokidi, Oyidie; Iglesias, Ignacio; Ikpoh, Margaret; Imberti, Davide; Ince, Hüseyin; Indolfi, Ciro; Ionova, Tatiana; Ip, John; Irles, Didier; Iseki, Harukazu; Ismail, Younus; Israel, Noah; Isserman, Steven; Iteld, Bruce; Ivanchura, Galina; Iyer, Ramakrishnan; Iyer, Venkat; Iza Villanueva, Ruben Omar; Jackson-Voyzey, Ewart; Jaffrani, Naseem; Jäger, Frank; Jain, Manish; James, Martin; Jamon, Yann; Jang, Sung Won; Jardim, Cesar Augusto Pereira; Jarmukli, Nabil; Jeanfreau, Robert; Jenkins, Ronald; Jiang, Xianyan; Jiang, Heng; Jiang, Tiemin; Jiang, Nan; Jimenez, Javier; Jobe, Robert; Joffe, Ian; Johansson, Bengt; Jones, Nick; Jorge, Jose Carlos Moura; Jouve, Bernard; Jundi, Mayar; Jung, Werner; Jung, Byung Chun; Jung, Kyung Tae; Kabbani, Samer; Kabour, Ameer; Kafkala, Chrystalenia; Kajiwara, Koji; Kalinina, Larisa; Kampus, Priit; Kanda, Junji; Kapadia, Shaival; Karim, Amin; Karolyi, Laszlo; Kashou, Hisham; Kastrup, Andreas; Katsivas, Apostolos; Kaufman, Elizabeth; Kawai, Kazuya; Kawajiri, Kenji; Kazmierski, John; Keeling, Phil; Kerfes, Galal Ali; Kerr Saraiva, José Francisco; Ketova, Galina; Khaira, Ajit; Khalid, Muhammad; Khludeeva, Elena; Khripun, Aleksey; Kim, Doo Il; Kim, Dae Kyeong; Kim, Nam Ho; Kim, Ki Seok; Kim, Young-Hoon; Kim, Jin bae; Kim, June Soo; Kim, Jeong Su; Kinova, Elena; Klein, Alexander; Kleinschnitz, Christoph; Kmetzo, James; Kneller, G. Larsen; Knezevic, Aleksandar; Koch, Stanley; Koenig, Kai; Koh, Su Mei Angela; Köhrmann, Martin; Koons, Jay; Korabathina, Ravikiran; Korennova, Olga; Koschutnik, Martin; Kosinski, Edward; Kovacic, Dragan; Kowalczyk, Jacek; Koziolova, Natalya; Kragten, J. A.; Krause, Lars Udo; Kreidieh, Imad; Krenning, B. J.; Krishnaswamy, Kannappan; Krysiak, Waldemar; Kuck, Karl-Heinz; Kumar, Somnath; Kümler, Thomas; Kuniss, Malte; Kuo, Jen-Yuan; Küppers, Achim; Kurrelmeyer, Karla; Kwan, Tak; Kyo, Eisho; Labovitz, Arthur; Lacroix, Alain; Lam, Andy; Lanas Zanetti, Fernando Tomas; Landau, Charles; Landini, Giancarlo; Lang, Wilfried; Larsen, Torben Bjerregaard; Laske, Volker; Lavandier, Karine; Law, Nicki; Lee, Moon Hyoung; Lee, Daniel; Leitão, Ana; Lejay, Dominique; Lelonek, Malgorzata; Lenarczyk, Radoslaw; Leprince, Patrick; Lequeux, Benoit; Leschke, Matthias; Ley, Nicolas; Li, Zicheng; Li, Yansheng; Li, Xiaodong; Li, Zhanquan; Li, Weihua; Liang, Jianqiu; Lieber, Ira; Lillestol, Michael; Limon Rodriguez, Ramon Horacio; Lin, Hailong; Lip, Gregory; Litchfield, Jennifer; Liu, Zhitao; Liu, Xuebo; Liu, Yalin; Liu, Feng; Liu, Wenhui; Llamas Esperon, Guillermo Antonio; Llisterri, Jose Luis; Lo, Ted; Lo, Eric; Lobos, Jose Maria; Lodde, Bernhard-Paul; Loiselet, Philippe; López-Sendón, José; Lorga Filho, Adalberto Menezes; Lori, Ido; Luo, Ming; Lupovitch, Steven; Lyrer, Philippe; M. Zuhairy, Hamed; Ma, Changsheng; Ma, Genshan; Ma, Hong; Madariaga, Irene; Maeno, Koji; Magnin, Dominique; Mahmood, Shahid; Mahood, Karen; Maid, Gustavo; Mainigi, Sumeet; Makaritsis, Konstantinos; Maldonado Villalon, José Arturo; Malhotra, Rohit; Malik, Amir; Mallecourt, Catherine; Mallik, Rajiv; Manning, Rickey; Manolis, Athanasios; Mantas, Ioannis; Manzur Jattin, Fernando Gabriel; Marcionni, Niccolo'; Marín, Francisco; Martín Santana, Antonio; Martinez, Jorge; Martinez, Luis; Maskova, Petra; Matadamas Hernández, Norberto; Matskeplishvili, Simon; Matsuda, Katsuhiro; Mavri, Alenka; May, Erik; Mayer, Nolan; Mazon, Pilar; McClure, John; McCormack, Terry; McGarity, William; McGuire, Michael; McIntyre, Hugh; McLaughlin, Paul; McLaurin, Brent; Medina Palomino, Feliz Alvaro; Mehta, Paresh; Mehzad, Reza; Meinel, Andreas; Melandri, Francesco; Mena, Amparo; Meno, Hirosi; Menzies, Dhananjai; Metcalf, Kneale; Meyer, Beat; Miarka, Jacek; Mibach, Frank; Michalski, Dominik; Michel, Patrik; Mihail Chreih, Rami; Mikdadi, Ghiath; Mikhail, Magdy; Mikus, Milan; Milicic, Davor; Militaru, Constantin; Miller, Gary; Milonas, Christos; Minescu, Bogdan; Mintale, Iveta; Miralles, Aurélien; Mirault, Tristan; Mistry, Dinesh; Mitchell, George; Miu, Nicoleta Violeta; Miyamoto, Naomasa; Moccetti, Tiziano; Mohammed, Akber; Mohd Nor, Azlisham; Molina de Salazar, Dora Ines; Molon, Giulio; Molony, David; Mondillo, Sergio; Mont, Lluis; Moodley, Rajendra; Moore, Roger; Moreira, Dalmo Antonio Ribeiro; Mori, Kiyoo; Moriarty, Andrew; Morka, Jacek; Moschos, Nikitas; Mota Gomes, Marco Antônio; Mousallem, Nicolas; Moya, Angel; Mügge, Andreas; Mulhearn, Thomas; Muller, Jean-Joseph; Muresan, Carmen Manuela; Muse, Derek; Musial, Wlodzimierz; Musumeci, Francesco; Nadar, Venkatesh; Nageh, Thuraia; Nair, Priya; Nakagawa, Hidemitsu; Nakamura, Yuichiro; Nakayama, Toru; Nam, Ki-Byeong; Napalkov, Dmitry; Natarajan, Indira; Nayak, Hemal; Nechvatal, Libor; Neiman, James; Nerheim, Pamela; Neuenschwander, Fernando Carvalho; Nishida, Kunihiro; Nizov, Alexey; Novikova, Tatiana; Novo, Salvatore; Nowalany-Kozielska, Ewa; Nsah, Emmanuel; Nunez Fragoso, Juan Carlos; Nyvad, Ole; Odin de Los Rios Ibarra, Manuel; O'Donnell, Martin; O'Donnell, Philip; Oh, Dong Jin; Oh, Yong Seog; Oh, Chia Theng Daniel; O'Hara, Gilles; Oikonomou, Kostas; Olalla, Juan Jose; Olivari, Zoran; Oliver, Richard; Olympios, Christoforos; Osborne, John; Osca, Joaquin; Osman, Raed; Osunkoya, Abayomi; Padanilam, Benzy; Panchenko, Elizaveta; Pandey, A. Shekhar; Paola, Angelo Amato Vicenzo de; Paraschos, Alexander; Pardell, Herbert; Park, Hyung Wook; Park, Jong Sung; Parkash, Ratika; Parker, Ian; Parrens, Eric; Parris, Robert; Passamonti, Enrico; Patel, Jaydutt; Patel, Rajesh; Pentz, William H.; Persic, Viktor; Perticone, Francesco; Peters, Patrick; Petkar, Sanjiv; Pezo, Luis Felipe; Pham, David; Phai, Gérald Phan Cao; Phlaum, Stephen; Pineau, Julien; Pineda-Velez, Armando; Pini, Riccardo; Pinter, Arnold; Pinto, Fausto; Pirelli, Salvatore; Pivac, Nediljko; Pizzini, Attilia Maria; Pocanic, Darko; Podoleanu, Cristian Gheorghe Calin; Polanczyk, Carisi Anne; Polasek, Petr; Poljakovic, Zdravka; Pollock, Stewart; Polo, Jose; Poock, James; Poppert, Holger; Porro, Yamile; Pose, Antonio; Poulain, François; Poulard, Jean-Ernst; Pouzar, Joe; Povolny, Petr; Pozzer, Domingo; Pras, Athanasios; Prasad, Neeraj; Prevot, Sébastien; Protasov, Konstantin; Prunier, Laurent; Puleo, John; Pye, Maurice; Qaddoura, Fatma; Quedillac, Jean-Michel; Raev, Dimitar; Rahimi, Sidiqullah; Raisaro, Arturo; Rama, Bhola; Ranadive, Nandkishore; Randall, Katie; Ranjith, Naresh; Raposo, Nuno; Rashid, Haroon; Raters, Christa; Rauch-Kroehnert, Ursula; Rebane, Thomas; Regner, Stefan; Renzi, Michael; Reyes Rocha, Miguel Agustin; Reza, Shabbir; Ria, Luigi; Richter, Dimitrios; Rickli, Hans; Rickner, Kyle; Rieker, Werner; Rigo, Fausto; Ripoll, Tomas; Ritt, Luiz Eduardo Fonteles; Roberts, Douglas; Rodríguez Pascual, Carlos; Rodriguez Briones, Ignacio; Rodriguez Reyes, Humberto; Roelke, Marc; Roman, Mark; Romeo, Francesco; Ronner, E.; Ronziere, Thomas; Rooyer, F. A.; Rosenbaum, David; Roth, Sherryn; Rozkova, Nadezda; Rubacek, Miroslav; Rubalcava, Frank; Rubanenko, Olesya; Rubin, Andrew; Ruiz Borret, Mariano; Rybak, Karin; Sabbour, Hani; Saenz Morales, Oscar; Sakai, Tetsuo; Salacata, Abraham; Salecker, Ilsbe; Salem, Adrien; Salfity, Marwan; Salguero, Rafael; Salvioni, Alessandro; Samson, Mercedes; Sanchez, Gregorio; Sandesara, Chirag; Saporito, Wladmir Faustino; Sasaoka, Taishi; Sattar, Payman; Savard, Daniel; Scala, Pierre-Jean; Scemama, Jacques; Schaupp, Thierry; Schellinger, Peter; Scherr, Carlos; Schmitz, Karl-Heinz; Schmitz, Bettina; Schmitz, Lisa; Schnitzler, Robert; Schnupp, Steffen; Schoeniger, Peter; Schön, Norbert; Schuster, Stefan; Schwimmbeck, Peter; Seamark, Clare; Seebass, Ruediger; Seidl, Karl-Heinz; Seidman, Barry; Sek, Jaroslaw; Sekaran, Lakshmanan; Seko, Yoshinori; Sepulveda Varela, Pablo Andres; Sevilla, Begoña; Shah, Vinay; Shah, Anil; Shah, Neerav; Shah, Aman; Shanes, Jeffrey; Sharareh, Ali; Sharma, Vijay Kumar; Shaw, Louise; Shimizu, Yutaka; Shimomura, Hideki; Shin, Dong Gu; Shin, Eun-Seok; Shite, Junya; Shoukfeh, Mohammad; Shoultz, Charles, III; Silver, Frank; Sime, Iveta; Simmers, T. A.; Singal, Dinesh; Singh, Narendra; Siostrzonek, Peter; Sirajuddin, Mohiburrahman; Skeppholm, Mika; Smadja, Didier; Smith, Richard; Smith, David; Soda, Hassan; Sofley, C. Wilson, Jr.; Sokal, Adam; Sotolongo, Rodolfo; Souza, Olga Ferreira de; Sparby, Jon Arne; Spinar, Jindrich; Sprigings, David; Spyropoulos, Alex; Stakos, Dimitrios; Steinberg, Alon; Steinwender, Clemens; Stergiou, Georgios; Stites, H. William; Stoikov, Anastas; Strasser, Ruth; Streb, Witold; Styliadis, Ioannis; Su, Guohai; Su, Xi; Suarez, Rafael Martin; Sudnik, Wanda; Sueyoshi, Atsushi; Sukles, Kai; Sun, Li; Suneja, Randeep; Svensson, Peter; Ziekenhuis, Antonius; Szavits-Nossan, Janko; Taggeselle, Jens; Takagi, Yuichiro; Takhar, Amrit; Tallet, Julio; Tamm, Angelika; Tanaka, Shozo; Tanaka, Katsumi; Tang, Aylmer; Tang, Sherman; Tassinari, Tiziana; Tayama, Shinji; Tayebjee, Muzahir; Tebbe, Ulrich; Teixeira, Jose; Tesloianu, Dan Nicolae; Tessier, Pascal; The, S. H.K.; Thevenin, Jérome; Thomas, Harold; Timsit, Serge; Topkis, Robert; Torosoff, Mikhail; Touze, Emmanuel; Traissac, Thalie; Trendafilova, Elina; Troyan, Barry; Tsai, Wenchi Kevin; Tse, Hung Fat; Tsutsui, Hiroshi; Tsutsui, Takashi; Tuininga, Y. S.; Turakhia, Minang; Turk, Samir; Turner, Wayne; Tveit, Arnljot; Twiddy, Shannon; Tytus, Richard; Ukrainski, Gerald; Valdovinos Chavez, Salvador Bruno; Van De Graaff, Eric; Vanacker, Peter; Vardas, Panagiotis; Vargas, Michael; Vassilikos, Vassilios; Vazquez, Juan; Venkataraman, Asok; Verdecchia, Paolo; Vester, Ernst Günter; Vial, Hubert; Vinereanu, Dragos; Vlastaris, Anthony; Vogel, Craig; vom Dahl, Jürgen; von Mering, Matthias; Vora, Kishor; Wakefield, Paul; Walia, Jasjit; Walter, Thomas; Wang, Mingsheng; Wang, Ningfu; Wang, Feng; Wang, Xinhua; Wang, Zulu; Wang, Kuo-Yang; Watanabe, Kouki; Wei, Jeanne; Weimar, Christian; Weinrich, Renate; Wen, Ming-Shien; Wheelan, Kevin; Wicke, Jens; Wiemer, Marcus; Wild, Beate; Wilke, Andreas; Willems, Stephan; Williams, Marcus; Williams, David; Winkler, Andreas; Wirtz, Jost Henner; Witzenbichler, Bernhard; Wong, Danny H K; Wong, Ka Sing Lawrence; Wong, Brian; Wozakowska-Kaplon, Beata; Wu, Zhaohui; Wu, Shulin; Wyatt, Nell; Xu, Yong; Xu, Xiangdong; Yamada, Akira; Yamamoto, Kazuya; Yamanoue, Hiroki; Yamashita, Takeshi; Yan, Ping Yen Bryan; Yang, Yanmin; Yang, Tianlun; Yao, Jing; Yarlagadda, Chakri; Yeh, Kuo-Ho; Yotov, Yoto; Yvorra, Serge; Zahn, Ralf; Zamorano, José; Zanini, Roberto; Zarich, Stuart; Zebrack, James; Zenin, Sergei; Zeuthen, Elisabeth Louise; Zhang, Xingwei; Zhang, Quansan; Zhang, Dadong; Zhang, Donghui; Zhang, Huanyi; Zhao, Shuiping; Zhao, Xinwen; Zheng, Yang; Zheng, Qiangsun; Zhou, Jing; Zhou, Jian; Zimmermann, Sergio Luiz; Zimmermann, Rainer; Zukerman, L. Steven; Zwaan van der, C. (TH Open, 2021)
Objective Anticoagulation management in patients with atrial fibrillation (AF) and impaired renal function is challenging. This study aimed to evaluate anticoagulation prescription patterns in relation to renal function and to describe 2-year clinical outcomes among dabigatran users.Methods Global Registry on Long-Term Oral Antithrombotic Treatment in Patients with Atrial Fibrillation (GLORIA-AF) is an international, prospective, and observational study program involving patients with newly diagnosed AF at risk for stroke. Prescription patterns were assessed by creatinine clearance (CrCl) at enrollment. Dabigatran users were followed for 2 years. Clinical outcomes were standardized for stroke and bleeding risk, based on CHA2DS2-VASc and HAS-BLED scores, with missing values imputed.Results Baseline CrCl values were available for 12,056 of 15,308 eligible patients (79%). With declining renal function, prescriptions increased for vitamin K antagonists (VKAs) and decreased for dabigatran (30–47% and 34–12%, respectively). The prescription of other non-vitamin K antagonists remained similar across CrCl groups (14–19%). In 4,873 dabigatran users, standardized stroke rates were low across all CrCl groups; 0.58/100 patient-years (95% confidence interval [CI]: 0.30–0.90) in CrCl ≥80 mL/min, 0.85 (95% CI: 0.48–1.21) in CrCl 50 to 79 mL/min, and 0.33 (95% CI: 0.06–1.11) in CrCl 30 to 49 mL/min. Similarly, major bleeding rates were low and numerically increased with declining renal function (0.68/100 patient-years, 95% CI: 0.39–1.03; 0.92, 95% CI: 0.58–1.32; and 1.26, 95% CI: 0.66–1.97, respectively).Conclusion In patients with AF, VKA prescriptions increased and dabigatran prescriptions decreased with declining renal function. Rates of stroke and major bleeding in dabigatran patients remained low across the categories of renal impairment.
Keywords: atrial fibrillation; anticoagulation; dabigatran; renal function; stroke; bleeding